The B cell-specific major raft protein, Raftlin, is necessary for the integrity of lipid raft and BCR signal transduction - Saeki, Kazuko (Oxford University Press, 2003)
Recent evidence indicates that membrane microdomains, termed lipid rafts, have a role in B-cell activation as platforms for B-cell antigen receptor (BCR) signal initiation. To gain an insight into the possible functioning of lipid rafts in B cells, we applied liquid chromatography electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS) methodologies to the identification of proteins that co-purified with lipid rafts of Raji cells. Among these raft proteins, we characterized a novel protein termed Raftlin (raft-linking protein). Like the Src family kinase, Raftlin is localized exclusively in lipid rafts by fatty acylation of N-terminal Gly2 and Cys3, and is co-localized with BCR before and after BCR stimulation. Disruption of the Raftlin gene in the DT40 B-cell line resulted in a marked reduction in the quantity of lipid raft components, including Lyn and ganglioside GM1, while overexpression of Raftlin increased the content of raft protein. Moreover, BCR-mediated tyrosine phosphorylation and calcium mobilization were impaired by the lack of Raftlin and actually potentiated by overexpression of Raftlin. These data suggest that Raftlin plays a pivotal role in the formation and/or maintenance of lipid rafts, therefore regulating BCR-mediated signaling.